Sounds like love - Poston, Ashley (Berkley Romance, 2025)
"A hitmaking songwriter and a bitter musician share a startling and inexplicable connection that they'll do anything to shake, in the next sparkling, magical book from Ashley Poston. Joni Lark is living the dream. She's one of the most coveted songwriters in LA...and she can't seem to write. There's an emptiness inside her, and nothing seems to fill it. When she returns to her hometown of Vienna Shores, North Carolina, she hopes that the sand, the surf, and the concerts at The Revelry, her family's music venue, will spark her inspiration. But when she gets there, nothing is how she left it. Her best friend is avoiding her, her mother's memories are fading fast, and The Revelry is closing. How can she think about writing her next song when everything is changing without her? Until she hears it. A melody in her head, lyric-less and half-formed, and an alluring and addictive voice to go with it-belonging, apparently, to a wry musician with hangups of his own. Surely, he's a figment of her overworked imagination. But then the very real man attached to the voice shows up in Vienna Shores. He's aggravating and gruff on the outside-nothing like the sweet, funny voice in Joni's head-and he has a plan: They'll finish the song haunting them both, break their connection, and hope they don't risk their hearts in the process. Because that song stuck in their heads? Maybe it's there for a reason"--